The Theology of Knowledge: A Study on the Definition of Knowledge Among the Early Mutakallimun - Ibrahim, Mohd Radhi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2011)
The aim of this article is to examine the definition of knowledge among the Mutakallimun and its relation to their theological doctrines. In this article I argued that the definitions of knowledge developed by the mutakallimun are influenced by their theological background. In addition, I will indicate that the theologians’ different views regarding “what a definition actually is and consists of” also play a key role in their definition of knowledge. To achieve this aim, I will investigate several definitions of knowledge from the Mutakallimun of Early Kalam from the early Ash’arites and the Mu’tazilites.